The degree of industrialized building systems implementation for projects in Malaysia / Nader Ardalan Abdul Ghani - Abdul Ghani, Nader Ardalan (2008)
Industrialized Building Systems (IBS) is a construction process that utilizes components or building systems which involve prefabricated components and on-site installation. From the structural classification, there are five main IBS groups identified as being used popularly in Malaysia. • Pre-cast Concrete Framing, Panel and Box Systems - pre-cast columns, beams, slabs, 3-D components (balconies, staircases, toilets, etc), etc; • Formwork Systems - tunnel forms, EPS-based forms, beams and columns moldings forms, permanent steel formworks, etc; • Steel Framing Systems - steel beams and columns, portal frames, roof trusses, etc; • Prefabricated Timber Framing Systems - timber frames, roof trusses, etc; • Block Work Systems - interlocking concrete masonry units (CMU), lightweight concrete blocks, etc. With the advancement of technology and innovation, various pre-fabricated materials Rave entered the market. It includes gypsum, wood wool, polymer, fiberglass, glass and aluminum-based IBS components. Currently a total of 128 IBS companies have registered with CIDB Malaysia.